2016
DOI: 10.1111/fwb.12788
|View full text |Cite
|
Sign up to set email alerts
|

Effects of silver nanoparticles on bacterioplankton in a boreal lake

Abstract: SUMMARY1. Silver nanoparticles (AgNPs) are widely used antimicrobial agents and a growing body of evidence suggests that their release into aquatic environments threatens natural bacterial communities and whole ecosystems. However, a knowledge gap exists between the toxic effects of AgNPs found in laboratory studies and their potential impacts in natural environments. 2. In an enclosure experiment conducted in a boreal lake, we exposed natural bacterial communities to AgNPs with two common types of coatings (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
(80 reference statements)
1
16
0
Order By: Relevance
“…Blakelock et al . () investigated the effects of silver nanoparticles (AgNP) on bacterioplankton in large enclosures of a boreal lake. One of the main outcomes of this study is that no toxic effects of AgNP on bacterioplankton were observed.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Blakelock et al . () investigated the effects of silver nanoparticles (AgNP) on bacterioplankton in large enclosures of a boreal lake. One of the main outcomes of this study is that no toxic effects of AgNP on bacterioplankton were observed.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…() and Blakelock et al . () underline the importance of considering environmental context and the specific properties of particles, and especially the biological complexity within ecosystems, to assess toxicity of ENPs.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our primary goals were to compare the temporal patterns of the response of a boreal lake grazingbased food web (microbes, phytoplankton, and zooplankton) to trophic Ag accumulation following chronic or pulse AgNP exposure and to assess the corresponding response of plankton-driven ecosystem metabolism over time scales capturing plankton food web dynamics. These goals were part of a larger experiment investigating the response of plankton biomass, diversity, and production to AgNP exposure and the behaviour of AgNPs in natural waters, the results of which are published elsewhere (Furtado et al 2014(Furtado et al , 2015Blakelock et al 2016;Vincent et al 2017). We predicted that (i) Ag accumulation would predict biotic responses and (ii) ecosystem function would reflect these responses and be maintained or recover quickly when exposed to chronic AgNP addition but be impaired after exposure to a pulse of AgNPs.…”
Section: Introductionmentioning
confidence: 99%